Linking Increasing Drought Stress to Scots Pine Mortality and Bark Beetle Infestations - Matthias Dobbertin; Beat Wermelinger; Christof Bigler; Matthias Bürgi; Mathias Carron; Beat Forster; Urs Gimmi; Andreas Rigling (The Scientific World Journal)
In the dry Swiss Rhone Valley, Scots pine forests have experienced increased mortality in recent years. It has commonly been assumed that drought events and bark beetles fostered the decline, however, whether bark beetle outbreaks increased in recent years and whether they can be linked to drought stress or increasing temperature has never been studied.